Cellular interaction influenced by surface modification strategies of gelatin-based nanoparticles. (February 2017) - Tse, Wai Hei; Gyenis, Laszlo; Litchfield, David W; Zhang, Jin
Theranostic applications of gelatin nanospheres require two major components, a method of detection and good biocompatibility. We characterized the response of UTA-6 human osteosarcoma cells to the introduction of functionalized 90 bloom-based gelatin nanospheres (158 ± 49 nm) modified with three elements in different order: (a) hybridization with cadmium-based quantum dots for optical detection, (b) bioconjugation with anti-human IgG FAB (anti-IgG) for cell targeting, with/without (c) capping with polyethylene glycol on the surface for enhanced biocompatibility. A one-pot process is developed for incorporating quantum dots and antibody with gelatin nanospheres. Path A of modifying gelatin nanospheres with quantum dots first followed by anti-IgG resulted in a significantly greater cellular viability than Path B with anti-IgG first followed by quantum dots. Capping with polyethylene glycol as the final step in modification yielded significantly opposing results with decreases in Path A and increases in Path B. Three-dimensional z-stacking fluorescent images of hybrid gelatin nanospheres with anti-IgG is observed to have an increase in cellular association. The observed results suggest the modification order for building hybrid nanospheres may have an impact on cellular response.